Interreligious dialogue: Identity versus openness - Petrov, George Daniel; Pleșa, Victor Marius (Technium Social Sciences Journal, 2021)
Interreligious dialogue is constantly proving its importance, especially in today’s society, where we find a multitude of religious offers, all claiming to be keepers or discoverers of the supreme truth. This does not mean a negotiation of the faith of each participant in the interreligious dialogue, but a knowledge of the other and his creed. The need for interreligious dialogue results from the pluralism of religions that society has in its composition, religions that are either revealed, as Christianity is, or that talk about impersonal powers man should aspire to through various forms of meditation. That is why it is imperative that Christian religions express their soteriological doctrine, from which ensues the most important relationship that can be achieved between God and man.